Ventriculosternal Shunt for the Treatment of Idiopathic Normal Pressure Hydrocephalus: A Case Report - Guo, Xinxia; Popal, Abdul Malik; Zhu, Zhoule; Cai, Chengwei; Lin, Jingquan; Jiang, Hongjie; Zheng, Zhe; Zhang, Jianmin; Shao, Anwen; Zhu, Junming (Frontiers in Surgery, 2021)
Background: Conventional corticospinal fluid (CSF) diversion surgery for idiopathic normal pressure hydrocephalus (iNPH) includes ventriculoperitoneal shunt and ventriculoatrial shunt. Ventriculosternal shunt may be considered if both the abdominal cavity and atrium are not feasible. Methods: A 76-year-old woman was admitted to our hospital with gait disturbance and urinary incontinence for two years, and aggravated for one month. Based on clinical assessment and imaging findings, the patient was diagnosed with iNPH, with surgical indications. She was on peritoneal dialysis for chronic renal failure, and a cardiac Doppler echocardiogram showed enlargement of the left atrium and decreased diastolic function of the left ventricle. Due to these conditions, we chose the sternum as the vessel for CSF absorption and performed ventriculosternal shunt. Results: No swelling, exudation, and effusion were found in the suprasternal fossa. Gait disturbance and urinary incontinence improved significantly immediately and one week after surgery, respectively. No shunt-related complication was reported at sixteen months follow-up. Conclusion: This case demonstrated ventriculosternal shunting as a feasible and alternative for the management of hydrocephalus.